Analisis Multidimensi Keberlanjutan Tanaman Jagung (Zea mays L.) di Kecamatan Herlang Kabupaten Bulukumba: Multidimensional Analysis of Corn (Zea mays L.) Sustainability In Herlang District Bulukumba Regency - Robbo, Anwar; Muliati Galib (Fakultas Pertanian Universitas Cokroaminoto Palopo, 2022)
Corn is one type of food crop known by many people because corn is one of the staple food ingredients with a variety of processed foods. In addition, corn can also be used as animal feed. There are many factors that affect the sustainability of corn cultivation. The purpose of this study were: (1) analyzing the sustainability of corn cultivation in Herlang of Bulukumba district; (2) analyzing the sensitive attributes to the sustainability of corn cultivation in Herlang of Bulukumba district. Based on the results of the analysis, the sustainability index value of corn cultivation were: ecological dimension 61.10%, social and cultural dimension 53.73% with a quite sustainable category, while the economic dimension is 40.15%. infrastructure and technology dimensions 44.12% and legal and institutional 44.59% with less sustainable categories. The results of the analysis of leverage 51 attributes, there are 17 sensitive attributes that affect the sustainability of corn in Herlang district, Bulukumba regency. Improvement of attributes, especially sensitive attributes, can improve corn sustainability index.